Anticipating words during spoken discourse comprehension: A large-scale, pre-registered replication study using brain potentials. (December 2020) - Nieuwland, Mante S.; Arkhipova, Yana; Rodríguez-Gómez, Pablo
Abstract: Numerous studies report brain potential evidence for the anticipation of specific words during language comprehension. In the most convincing demonstrations, highly predictable nouns exert an influence on processing even before they appear to a reader or listener, as indicated by the brain's neural response to a prenominal adjective or article when it mismatches the expectations about the upcoming noun. However, recent studies suggest that some well-known demonstrations of prediction may be hard to replicate. This could signal the use of data-contingent analysis, but might also mean that readers and listeners do not always use prediction-relevant information in the way that psycholinguistic theories typically suggest. To shed light on this issue, we performed a close replication of one of the best-cited ERP studies on word anticipation (Van Berkum, Brown, Zwitserlood, Kooijman & Hagoort, 2005; Experiment 1), in which participants listened to Dutch spoken mini-stories. In the original study, the marking of grammatical gender on pre-nominal adjectives ('groot/grote') elicited an early positivity when mismatching the gender of an unheard, highly predictable noun, compared to matching gender. The current pre-registered study involved that same manipulation, but used a novel set of materials twice the size of the original set, an increased sample size (N = 187), and Bayesian mixed-effects model analyses that better accounted for known sources of variance than the original. In our study, mismatching gender elicited more negative voltage than matching gender at posterior electrodes. However, this N400-like effect was small in size and lacked support from Bayes Factors. In contrast, we successfully replicated the original's noun effects. While our results yielded some support for prediction, they do not support the Van Berkum et al. effect and highlight the risks associated with commonly employed data-contingent analyses and small sample sizes. Our results also raise the question whether Dutch listeners reliably or consistently use adjectival inflection information to inform their noun predictions.